Analisis Pengaruh Likuiditas dan Profitabilitas terhadap Financial Distress Menggunakan Model Altman Z-Score : Studi pada Perusahaan Sub Sektor Minyak dan Gas Bumi Periode 2018 – 2023 - Jhonni Sinaga; Nikken Syakira Haq; Supriyanto Supriyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Analysis of financial distress is carried out to identify early signs of financial difficulties experienced by the company. Determining the number of samples used the purposive sampling method. The type of data used is secondary data obtained from the source www.idx.co.id. The analytical method used is statistical analysis consisting of descriptive statistical analysis, multiple linear regression analysis, classical assumption testing, and hypothesis testing. The results of partial hypothesis testing stated that liquidity measured by the current ratio had no significant effect on financial distress with a tcount value of 2.010 > ttable 1.70562 and liquidity measured by the quick ratio had no significant effect on financial distress with a tcount value of -0.027 < ttable 1.70562. while profitability measured by return on assets has a significant effect on financial distress with a value of tcount 5.453 > ttable 1.70562 and profitability measured by return on equity has no significant effect on financial distress with a value tcount < ttable or 1.201 < 1.70562. The research results of simultaneous hypothesis testing stated that liquidity and profitability simultaneously had a significant effect on financial distress with a value of fcount > ftable or 16.355 > 2.98. The research results show that the coefficient of determination (Adjusted R Square) is 0.679, which means that the influence of the liquidity and profitability variables on financial distress is 67.9%.